A Positive Legacy of Trauma? The Role of Perceived Social Support on Mental Health Among Earthquake Survivors During the COVID-19 Outbreak - Wang, Dongfang; Zhai, Shuyi; Chen, Jiaqiao; Chen, Yao; Hua, Shiming; Wang, Chengchen; Fan, Fang; Liu, Xianchen (Frontiers in Psychiatry, 2022)
Background People with prior experience of severe trauma may be particularly vulnerable in the face of the COVID-19 pandemic. However, little is known about mental health problems among prior trauma survivors during the pandemic outbreak. Methods A total of 362 Wenchuan earthquake survivors were assessed using Patient Health Questionnaire, Generalized Anxiety Disorder Scale, as well as Multidimensional Scale of Perceived Social Support, as part of an online survey between February 3 and 10, 2020. Results Our results showed that 6.6 and 4.7% of the participants experienced depression and anxiety during the COVID-19 outbreak, respectively. Perceived social support was negatively associated with depressive and anxiety symptoms. Earthquake exposure has no direct effect on current depressive and anxiety symptoms, but it would moderate the direct relationship between perceived social support and psychological symptoms. Conclusions Our findings suggested that trauma exposure may lead to salutogenic outcomes. The protective effect of perceived social support on psychological symptoms was greater in people with a higher level of trauma exposure than in a lower one.